1868 Kan. Gen Stat. 378 - (:unkn) unknown (My University, 1868)
§ 282: Prohibited carrying a pistol, bowie-knife, dirk, or other deadly weapon while engaged in illegitimate business, under the influence of intoxicating drinks, or engaged in insurrection against the United States. Violators guilty of a misdemeanor, fined not exceeding one hundred dollars, or imprisoned not exceeding three months, or both fine and imprisonment.
Keywords: POSSESSION - DANGEROUS PERSONS; CARRY - INTENT TO COMMIT CRIME